In vitro evaluation of shear bond strength of orthodontic brackets bonded with different adhesives - Deepak Singh; Divya Swarup; Neha Kumari; Subhash Kumar; Tanu Priya; Ritama Sinha (Wolters Kluwer Medknow Publications, 2023)
Background: To endure the orthodontic forces used throughout treatment, the bond strength of bonded orthodontic brackets must be enough with assessment of shear bond strength when bonding orthodontic brackets with various adhesives. Materials and Methods: Overall, forty extracted premolars due to orthodontic treatment were included. They were split into four equal cohorts with various primers. With both adhesives, shear bond strength had been assessed with and without salivary contamination. SPSS software was used to assess the outcomes. Consideration was given to statistical significance of P value of less than 0.05. Results: Several groups' average bond strengths in MPa were assessed in both dry and contaminated saliva conditions. When it was dry, Transbond Plus demonstrated greater shear bond strength. Conclusion: Hydrophilic Transbond Plus resin outperformed hydrophobic Transbond XT resin in terms of shear bond strength under both situations.